Am I blue? coming out from the silence - Bauer, Marion Dane. (New York HarperCollins, 1995)
A collection of short stories about homosexuality by such authors as Bruce Coville, M.E. Kerr, William Sleator, and Jane Yolen.
Introduction -- Am I blue? Bruce Coville -- We might as well all be strangers M.E. Kerr -- Winnie and Tommy Francesca Lia Block -- Slipping away Jacqueline Woodson -- The honorary shepherds Gregory Maguire -- Running Ellen Howard -- Three Mondays in July James Cross Giblin -- Parents' night Nancy Garden -- Michael's little sister C.S. Adler -- Supper Leslea? Newman -- Holding Lois Lowry -- Blood sister Jane Yolen -- Hands Jonathan London -- 50% chance of lightning Cristina Salat -- In the tunnels William Sleator -- Dancing backwards Marion Dane Bauer.
Gay, Lesbian, and Bisexual Book Award (American Library Association), 1995
Lambda Literary Award, 1994
Keywords: Homosexuality -- Juvenile fiction; Short stories, American; Homosexuality -- Fiction; Short stories